High-temperature-resistant spraying material for metal surface as well as preparation method and application of high-temperature-resistant spraying material
By spraying high-temperature resistant materials on the inner wall of the square tube to form a dense glaze surface, the problem of coke oven waste gas condensation is solved, the heat exchange efficiency and equipment life are improved, and the acid-base corrosion and electrostatic adsorption effect is achieved.
Patent Information
- Application Number
- CN202311538816.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-17
- Publication Date
- 2024-12-20
AI Technical Summary
When the coke oven waste gas flows in the square tube heat exchanger, due to the rough surface of the inner wall of the square tube, coal tar and coke oven coal powder condense at low temperatures, resulting in a decrease in heat exchange efficiency and the condensate is difficult to clean, affecting the equipment life.
Using a high-temperature spraying material for metal surfaces, including barium carbonate, sodium carbonate, titanium dioxide, silicate cement, copper powder and hydroxyapatite, it is sprayed and sintered at high temperature to form a dense and smooth glaze. Reduce the adhesion of condensate and improve bond strength and acid resistance by adjusting the ratio and adding ingredients such as sodium fluoride.
The formed glaze surface has good high temperature resistance, acid and alkali corrosion resistance and electrostatic adsorption effects, which reduces condensate adhesion, improves heat exchange efficiency, extends the service life of the equipment, and ensures stability and easy cleaning in high-temperature environments.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal surface protection, and more specifically, to a high temperature resistant spraying material for metal surface and a preparation method and application thereof. Background Art
[0002] In the coke oven raw gas waste heat recovery system, it is usually necessary to use a square tube heat exchanger for heat recovery. The square tube heat exchanger is a partition-type heat exchanger that uses the wall of the tube bundle enclosed in the shell as the heat transfer surface. Its working principle is that there are two pipeline loops inside the heat exchanger, that is, the heat source is connected to the tube side and the cold source is connected to the shell side to achieve heat exchange.
[0003] At present, the temperature of coke oven raw gas itself is very high, which can reach 800-900℃. When the relevant square tube heat exchanger recovers the waste heat of coke oven raw gas, the coke oven raw gas is introduced into the tube side of the square tube heat exchanger, and the circulating cooling water is introduced into the shell side of the square tube heat exchanger. The square tube wall is used as the heat transfer surface to realize heat exchange, thereby realizing the effect of waste heat recovery of coke oven raw gas. When the square tube heat exchanger is performing heat exchange work, the tube wall temperature can reach 400-500℃.
[0004] With regard to the above-mentioned related technologies, the inventors believe that when the coke oven raw gas flows in the square tube of the heat exchanger, since the square tube is made of metal, its inner wall surface is relatively rough, and the coal tar and fine coke oven coal powder carried in the high-temperature coke oven raw gas will condense after contacting the low-temperature inner wall of the square tube, forming a large amount of condensate on the inner wall of the square tube. As the condensed material accumulates on the inner wall of the square tube, the heat exchange efficiency of the heat exchanger will be seriously affected. Summary of the invention
[0005] In order to reduce the adhesion of condensed matter on the inner wall of the square tube and ensure the heat exchange effect of the square tube heat exchanger, the present application provides a high-temperature resistant spray material for metal surface and a preparation method and application thereof.
[0006] In the first aspect, the present application provides a high temperature resistant spraying material for metal surface, which adopts the following technical solution: A high temperature resistant spraying material for metal surface, comprising the following powders in parts by weight: Barium carbonate 10-20 parts; 10-20 parts of sodium carbonate; 15-25 parts of titanium dioxide; 5-10 parts of Portland cement; 30-50 parts of copper powder; Hydroxyapatite 5-15 parts.
[0007] By adopting the above technical scheme, the spraying material is sprayed on the surface of the metal blank and then sintered to form a dense and smooth glaze on the surface of the metal blank, thereby reducing the adhesion of coal tar and fine coke oven coal powder to the tube wall, facilitating the cleaning of the inner wall of the light tube, and ensuring the heat exchange effect of the heat exchanger; since the metal blank will experience thermal expansion during the high-temperature sintering process, it is necessary to adjust the thermal expansion coefficient of the spraying material to be smaller than and close to the thermal expansion coefficient of the metal blank, so that the spraying material is tightly combined with the metal blank after high-temperature sintering, ensuring that the square tube in the square tube heat exchanger has good high temperature resistance when used in an environment of 400-500°C, and is not prone to falling off or melting.
[0008] In the present application, barium carbonate, sodium carbonate, titanium dioxide, silicate cement, copper powder and hydroxyapatite are added to work synergistically and their ratios are adjusted, so that the prepared spraying material can meet the use requirements of a thermal expansion coefficient close to that of the metal blank; since the powders in the spraying material are mostly inorganic substances and the bonding effect between the spraying material and the metal blank is poor, the titanium dioxide and silicate cement jointly play a bonding role, so that the spraying material can be stably bonded to the surface of the metal blank after being sprayed onto the metal surface, reducing the displacement of the spraying material and ensuring the formation of a stable and uniform glaze film during the firing process.
[0009] In addition, as the spray material is sintered at a higher temperature on the surface of the metal body, the sodium carbonate melts during the sintering process and can further penetrate into the rough surface of the metal body. The melted sodium carbonate has a strong bonding effect, which further enhances the bonding effect between the spray material and the metal body in a high temperature environment, forming a glaze film with strong bonding strength, ensuring that it can adapt to the high temperature environment of coke oven raw gas when used in a heat exchanger.
[0010] The main component of titanium dioxide is titanium dioxide. During the sintering process, titanium dioxide reacts with barium carbonate to form barium titanate. Sodium carbonate plays a role of flux catalysis, reducing the reaction temperature of titanium dioxide and barium carbonate. The formation of barium titanate further enhances the density of the glaze film, reduces the formation of pores in the glaze film during the firing process, makes the formed glaze surface smoother, and reduces the adhesion of condensate on the glaze surface. Even if there is condensate staying inside the square tube, it is not easy to combine with the glaze surface, which is convenient for the subsequent cleaning of the inner wall of the square tube, thereby ensuring the heat exchange effect of the heat exchanger; and the formation of barium titanate can further enhance the mechanical strength of the glaze surface, reduce the occurrence of cracking on the glaze surface, and make the glaze surface tightly combined with the metal body.
[0011] Copper powder and hydroxyapatite are both materials with thermal expansion coefficients close to that of metal blanks, so that the spraying material can be tightly solidified on the surface of the metal blank after sintering. The copper powder can form a flexible and low-porosity glaze film during the sintering process, which ensures the bonding strength between the glaze layer and the metal blank, while reducing the erosion of the condensate, making the glaze surface resistant to acid and alkali corrosion.
[0012] During the flow of raw coke oven gas on the inner wall of the square tube, friction static electricity may be generated on the inner wall of the square tube, causing the fine coke oven coal powder in the coke oven gas to adhere to the inner wall of the square tube due to electrostatic adsorption. The barium titanate produced by the reaction of titanium dioxide and barium carbonate is a strong dielectric compound material, and combined with copper powder, it can transfer the static electricity generated on the inner wall of the square tube, making the glaze surface have an anti-static adsorption effect, thereby reducing the deposition and adsorption of coke oven coal powder on the inner wall of the square tube, so that the square tube heat exchanger maintains a good heat exchange effect.
[0013] Preferably, the powder comprises the following parts by weight: Barium carbonate 12-18 parts; 13-17 parts of sodium carbonate; 18-23 parts of titanium dioxide; 7-9 parts of Portland cement; 35-45 parts of copper powder; Hydroxyapatite 8-13 parts.
[0014] By adopting the above technical solution and further adjusting the raw material ratio of the spraying material, the spraying material can have a good bonding effect with the metal blank during the sintering process to form a smooth and dense glaze surface, thereby improving the heat exchange effect of the square tube heat exchanger during operation.
[0015] Preferably, 15-20 parts of sodium fluoride are also included.
[0016] By adopting the above technical solution, sodium fluoride is added to the spraying material. On the one hand, it helps to promote the rapid solidification of silicate cement, form a stable glaze layer during the drying process of the metal body, and then form a dense and uniform glaze surface after firing; on the other hand, since the condensate in the coke oven raw gas is acidic, sodium fluoride can react with hydroxyapatite to form fluoroapatite, enhance the acid resistance of the glaze, reduce the corrosion of the condensate to the metal square tube, and extend the service life of the square tube.
[0017] Preferably, the copper powder is diatomaceous earth-loaded copper powder, and its preparation method comprises the following steps: The diatomaceous earth is placed in a hydrochloric acid solution, shaken in a constant temperature water bath, and then washed with water until neutral to obtain pretreated diatomaceous earth. The pretreated diatomaceous earth is dispersed in an ethanol solution, and copper powder is added. The weight ratio of copper powder to diatomaceous earth is 1: (1.1-1.2). Ultrasonic shaking is performed for 1-2 hours, and then filtration and drying are performed to obtain diatomaceous earth-loaded copper powder.
[0018] By adopting the above technical scheme, in order to further improve the mixing effect of copper powder and other inorganic powders, the copper powder is added in the form of being loaded in diatomaceous earth. After the diatomaceous earth adsorbs the copper powder, it is fired with other spraying materials. The diatomaceous earth can reduce the oxidation of the copper powder during the initial heating process, thereby ensuring that more copper powder forms a dense and strong glaze during the firing process, thereby enhancing the bonding with the metal body; and the diatomaceous earth contains a large amount of amorphous silicon dioxide, which undergoes a crystal transformation during the firing process to form crystalline silicon dioxide, accompanied by volume expansion, so that the silicon dioxide and the copper powder have a tight bonding effect, which helps the thermal expansion coefficients of the spraying material and the metal body to be close, thereby helping to form a dense glaze with good bonding with the metal body after sintering.
[0019] Preferably, the particle size of the diatomaceous earth-loaded copper powder is 40-60 μm.
[0020] By adopting the above technical solution, when the particle size of the diatomite-loaded copper powder is within this range, the spraying material and the metal blank have a better bonding effect after firing, and the formed glaze has better density and wear resistance.
[0021] In a second aspect, the present application provides a method for preparing a high temperature resistant spraying material for a metal surface, using the following technical solution: A method for preparing a high temperature resistant spraying material for a metal surface comprises the following steps: Barium carbonate, sodium carbonate, titanium dioxide, silicate cement, copper powder, hydroxyapatite and sodium fluoride are weighed in proportion, and then ground and mixed at a grinding speed of 200-220 rpm and a mixing time of 15-20 min. After mixing, the mixture is sieved to obtain a powder with uniform particles.
[0022] By adopting the above technical scheme, the powder after grinding and mixing is more uniform, and after the slurry made of the above powder is sprayed on the surface of the metal blank, it can have good bonding strength with the metal blank during high-temperature sintering and is not easy to fall off. When the sprayed material is sintered on the surface of the metal blank and used in a high-temperature environment of 400-500°C, it has the advantages of being smooth, easy to clean, high-temperature resistant, acid and alkali resistant, and having a high bonding strength with the metal blank.
[0023] In a third aspect, the present application provides an application of a high temperature resistant spraying material for a metal surface, using the following technical solution: An application of a high temperature resistant spraying material for a metal surface comprises the following steps: S1. Mix the powder and water in a certain proportion to obtain a slurry, and adjust the water content of the slurry to 50%-55%; S2, spraying the slurry evenly on the metal body through a spraying device to form a glaze film with a thickness of 0.2-0.4 mm; S3. The sprayed metal body is dried and then sintered at a high temperature. Nitrogen is introduced during the sintering process. The sintering temperature is 1050-1090°C and the temperature is kept for 10-12 hours to form a dense glaze surface on the surface of the metal body.
[0024] By adopting the above technical scheme, the spraying material is applied to the surface of the metal blank, and a dense glaze is formed on the surface of the metal blank after spraying-drying-sintering, thereby improving the problem of condensation easily adhering to the surface of the metal blank when used in a high-temperature environment, reducing the problem of thermal conductivity efficiency caused by condensation deposition, and the glaze has good bonding strength with the metal blank at high temperatures and has good stability when used at high temperatures.
[0025] Preferably, the metal blank in S2 is 310S stainless steel, and the thermal expansion coefficient of the 310S stainless steel is 18.7 μm / m·K.
[0026] By adopting the above technical solution, the square tube in the square tube heat exchanger is made of 310S stainless steel, which is austenitic chromium-nickel stainless steel, has excellent oxidation resistance and corrosion resistance, can operate continuously at high temperature, and has good high temperature resistance.
[0027] In summary, this application has the following beneficial effects: 1. Due to the synergistic effect of barium carbonate, sodium carbonate, titanium dioxide, silicate cement, copper powder and hydroxyapatite in the present application and the adjustment of their ratio, the prepared spraying material can meet the use requirements close to the thermal expansion coefficient of the metal blank; since the powder in the spraying material is mostly inorganic, the bonding effect between it and the metal blank is not good, the titanium dioxide and silicate cement jointly play a bonding role, so that the spraying material can be stably bonded to the surface of the metal blank after being sprayed to the metal surface, reducing the displacement of the spraying material and ensuring the formation of a stable and uniform glaze film during the firing process.
[0028] 2. Sodium fluoride is preferably used in the present application. On the one hand, it helps to promote the rapid solidification of silicate cement, form a stable glaze layer during the drying process of the metal body, and then form a dense and uniform glaze surface after firing; on the other hand, since the condensate in the coke oven raw gas is acidic, sodium fluoride can react with hydroxyapatite to form fluoroapatite, enhance the acid resistance of the glaze, reduce the corrosion of the condensate to the metal square tube, and extend the service life of the square tube.
[0029] 3. The application method of the present application applies the spray material to the surface of the metal blank, and forms a dense glaze on the surface of the metal blank after spraying-drying-sintering, thereby improving the problem of condensation easily adhering to the surface of the metal blank when used in a high-temperature environment, reducing the problem of thermal conductivity caused by condensation deposition, and the glaze has good bonding strength with the metal blank at high temperatures and has good stability when used at high temperatures. DETAILED DESCRIPTION
[0030] Source of raw materials: The metal blanks in this application specification all refer to 310S stainless steel, and its physical and chemical properties are as follows: 310S stainless steel refers to austenitic chromium-nickel stainless steel, with a melting point of 1470°C, a tensile strength of ≥520Mpa; a yield strength of ≥205Mpa; a thermal expansion coefficient of 18.7μm / m·K; Chemical composition: C:≤0.08, Si:≤1.500, Mn:≤2.00, P:≤0.035, S:≤0.030, Ni:≤19.00-22.00, Cr:≤24.00-26.00; Copper powder CAS number: 7440-50-8, particle size 0.1-0.2μm; Barium carbonate CAS number: 513-77-9, powder particle size 300 mesh; Sodium carbonate CAS number: 497-19-8, powder particle size 400 mesh; Titanium dioxide CAS number: 13463-67-7, powder particle size 400 mesh; Portland cement CAS number: 1327-39-5, powder particle size 300 mesh; Hydroxyapatite CAS number: 12167-74-7, powder particle size 300 mesh; Sodium fluoride CAS number: 7681-49-4, powder particle size 300 mesh. Example
[0031] Examples 1.1-1.5 A high temperature resistant spraying material for metal surface, comprising the following weights of powder: Barium carbonate 10-20kg; Sodium carbonate 10-20kg; Titanium dioxide 15-25kg; Portland cement 5-10kg; Copper powder 30-50kg; Hydroxyapatite 5-15kg.
[0032] The dosage ratio of the spraying material raw materials in Examples 1.1-1.5 is shown in Table 1.
[0033] Table 1. Ratio of raw materials used in spraying materials of Examples 1.1-1.5 (unit: kg) Example 1.1 Example 1.2 Example 1.3 Example 1.4 Example 1.5 Barium carbonate 10 12 15 18 20 Sodium carbonate 10 13 15 17 20 Titanium dioxide 15 18 20 23 25 Portland cement 5 7 8 9 10 Copper powder 30 35 40 45 50 Hydroxyapatite 5 8 11 13 15 The method for preparing a high temperature resistant spraying material for a metal surface comprises the following steps: Barium carbonate, sodium carbonate, titanium dioxide, silicate cement, copper powder and hydroxyapatite were weighed in proportion, and then ground and mixed at a grinding speed of 220 rpm and a mixing time of 20 min. After mixing, the mixture was sieved through a 200-mesh sieve to obtain a powder with uniform particles.
[0034] Examples 2.1-2.3 A high temperature resistant spraying material for metal surface, based on Example 1.3, the difference is that 15-20 kg of sodium fluoride is also added to the powder; The amount of sodium fluoride added in Example 2.1 is 15 kg; The amount of sodium fluoride added in Example 2.2 is 18 kg; The amount of sodium fluoride added in Example 2.3 is 20 kg.
[0035] The method for preparing a high temperature resistant spraying material for a metal surface comprises the following steps: Barium carbonate, sodium carbonate, titanium dioxide, silicate cement, copper powder, hydroxyapatite and sodium fluoride were weighed in proportion, and then ground and mixed at a grinding speed of 220 rpm and a mixing time of 20 min. After mixing, the mixture was sieved through a 200-mesh sieve to obtain a powder with uniform particles.
[0036] Example 3 A high temperature resistant spraying material for metal surface, based on Example 2.2, except that the copper powder is replaced by an equal amount of diatomaceous earth loaded copper powder; the particle size of the added diatomaceous earth loaded copper powder is 50 μm; The preparation method of diatomite-loaded copper powder comprises the following steps: The diatomaceous earth was placed in a 3 mol / l hydrochloric acid solution, shaken in a constant temperature water bath for 15 min, and then washed with water until neutral to obtain pretreated diatomaceous earth. The pretreated diatomaceous earth was dispersed in an ethanol solution, and copper powder was added. The weight ratio of copper powder to diatomaceous earth was 1:1.1. Ultrasonic shaking was performed for 1.5 h, and then filtered and dried to obtain diatomaceous earth-loaded copper powder.
[0037] Examples 4.1-4.4 A high temperature resistant spraying material for metal surface, which is different from Example 3 in that the particle size of the added diatomaceous earth loaded copper powder is different.
[0038] The particle size of the diatomaceous earth-loaded copper powder added in Example 4.1 is 40 μm; The particle size of the diatomaceous earth-loaded copper powder added in Example 4.2 is 60 μm; The particle size of the diatomaceous earth-loaded copper powder added in Example 4.3 is 20 μm; The particle size of the diatomaceous earth-loaded copper powder added in Example 4.4 is 80 μm.
[0039] Comparative Example Comparative Example 1 A high temperature resistant spraying material for metal surface, which is different from Example 1.3 in that the amount of barium carbonate used is 0 kg.
[0040] Comparative Example 2 A high temperature resistant spraying material for metal surface, which is different from Example 1.3 in that the amount of sodium carbonate used is 0 kg.
[0041] Comparative Example 3 A high temperature resistant spraying material for metal surface, which is different from Example 1.3 in that the amount of titanium dioxide used is 0 kg.
[0042] Comparative Example 4 A high temperature resistant spraying material for metal surface, which is different from Example 1.3 in that the amount of silicate cement used is 0 kg.
[0043] Comparative Example 5 A high temperature resistant spraying material for metal surface, which is different from Example 1.3 in that the amount of copper powder used is 0 kg.
[0044] Comparative Example 6 A high temperature resistant spraying material for metal surface, which is different from Example 1.3 in that the amount of hydroxyapatite is 0 kg; Comparative Example 7 A high temperature resistant spraying material for metal surface, which is different from Example 1.3 in that an equal amount of calcium carbonate is used to replace sodium carbonate.
[0045] Comparative Example 8 A high temperature resistant spraying material for metal surface, which is different from Example 1.3 in that an equal amount of silver powder is used to replace copper powder.
[0046] Comparative Example 9 A high temperature resistant spraying material for metal surface, which is different from Example 1.3 in that hydroxyapatite is replaced by an equal amount of bentonite.
[0047] Application Examples Application Examples 1.1-1.5 An application of a high temperature resistant spraying material for a metal surface comprises the following steps: S1. Mix the powder and water in a certain proportion to obtain a slurry, and adjust the water content of the slurry to 50%; S2, spraying the slurry in S1 evenly on the metal body through a spraying device to form a glaze film with a thickness of 0.3 mm; S3, the metal body after spraying is dried and then sintered at a high temperature, nitrogen is introduced during the sintering process, the sintering temperature is 1080°C, and the temperature is kept for 12 hours, so that the glaze film forms a dense glaze surface on the surface of the metal body; The powder in S1 is prepared according to Examples 1.1-1.5; the metal blank in S2 is 310S stainless steel, and the thermal expansion coefficient of the 310S stainless steel is 18.7 μm / m·K.
[0048] Application Examples 2.1-2.3 An application of a high temperature resistant spraying material for a metal surface is different from Application Example 1.3 in that the powder in S1 is prepared by Examples 2.1-2.3.
[0049] Application Example 3 An application of a high temperature resistant spray material for a metal surface is different from Application Example 2.2 in that the powder in S1 is prepared by Examples 5.1-5.3.
[0050] Application Examples 4.1-4.4 An application of a high temperature resistant spraying material for a metal surface is different from Application Example 3 in that the powder in S1 is prepared by Examples 4.1-4.4.
[0051] Comparative Application Examples 1-9 The application of a high temperature resistant spray material for metal surface is different from that of Application Example 1.3 in that the powder in S1 is prepared in sequence from Comparative Examples 1-9.
[0052] Performance testing The tests include: 1. Bonding strength test The sintered metal bodies with sprayed materials of Application Examples 1-7 and Comparative Application Examples 1-6 are made into test pieces, and the test pieces are installed in a vibrator. The flat impact hammer on the vibrator is used to continuously hammer the glaze on the surface of the sample at a frequency of 500 times per minute. The time when the glaze on the hammered part appears delamination or peeling is tested. The longer the anti-hammering time is, the better the bonding strength between the glaze and the metal body is.
[0053] 2. Condensation adhesion test A metal billet tube with a sprayed material sintered on the inner wall is used in a square tube heat exchanger. Coke oven raw gas is introduced into the tube as a heat source, and circulating cooling water is introduced outside the tube. The temperature of the coke oven raw gas itself is 800-900°C. When the tubular heat exchanger is working, the wall temperature of the square tube is maintained at around 500°C. After the square tube heat exchanger has been working for 72 hours, the square tube is removed, and the weight of the square tube before and after the heat exchange is weighed and the weight difference is calculated. The larger the weight difference, the more condensate is attached to the tube.
[0054] The metal tubes without any treatment were used in the square tube heat exchanger as the control group, and the condensate adhesion test results were observed.
[0055] The test results are shown in Table 2. Table 2 Test results of application examples 1-4 and comparative application examples 1-9 The time it takes for the hammered part of the glaze to peel off / min Square tube weight difference before and after heat exchange / g Application Example 1.1 44 82 Application Example 1.2 45 81 Application Example 1.3 46 80 Application Example 1.4 45 81 Application Example 1.5 45 82 Application Example 2.1 50 78 Application Example 2.2 52 77 Application Example 2.3 51 78 Application Example 3 58 73 Application Example 4.1 57 75 Application Example 4.2 57 75 Application Example 4.3 55 77 Application Example 4.4 55 78 Comparative application example 1 30 102 Comparative Application Example 2 34 110 Comparative Application Example 3 30 115 Comparative Application Example 4 32 103 Comparative Application Example 5 28 123 Comparative Application Example 6 29 100 Comparative Application Example 7 30 105 Comparative Application Example 8 25 130 Comparative Application Example 9 33 104 Control group * 220 3. Corrosion resistance test The metal blanks sintered with sprayed materials and the untreated metal blanks in Application Example 1.1 and Application Example 2.2 were made into test pieces respectively, and immersed in a 5wt% acidic sulfuric acid solution to observe whether there were obvious changes.
[0056] The test results are shown in Table 3. Table 3 Corrosion resistance test results Corrosion resistance test Application Example 1.1 No significant changes on 13d Application Example 2.2 No significant changes at 17 days Untreated metal blank No significant changes after 10 days From Application Examples 1.1-1.5 and Table 2, it can be seen that Application Example 1.3 is a better application example. In this application, barium carbonate, sodium carbonate, titanium dioxide, silicate cement, copper powder and hydroxyapatite are added to act synergistically and their ratios are adjusted so that the prepared spraying material can meet the use requirements close to the thermal expansion coefficient of the metal blank; since the powder in the spraying material is mostly inorganic and the bonding effect with the metal blank is not good, titanium dioxide and silicate cement jointly play a bonding role, so that the spraying material can be stably bonded to the metal surface after being sprayed to the metal surface, reducing the displacement of the spraying material and ensuring the formation of a stable and uniform glaze film during the firing process.
[0057] It can be seen from the combination of application example 1.3 and comparative application examples 1-9 and Table 2 that the addition of titanium dioxide, barium carbonate and sodium carbonate in the present application has a synergistic effect, which helps to form barium titanate during the sintering process, further enhances the density of the glaze film, reduces the formation of pores in the glaze film during the sintering process, makes the formed glaze surface smoother, reduces the adhesion of condensate on the glaze surface, and even if there is condensate staying inside the square tube, it is not easy to combine with the glaze surface, which is convenient for the subsequent cleaning of the inner wall of the square tube, thereby ensuring the heat exchange effect of the heat exchanger; and the formation of barium titanate can further enhance the mechanical strength of the glaze surface, reduce the occurrence of cracks on the glaze surface, and make the glaze surface tightly combined with the metal body; Copper powder and hydroxyapatite are materials with thermal expansion coefficients close to that of metal blanks, so that the spraying material can be tightly solidified on the surface of the metal blank after sintering. Copper powder can form a flexible and low-porosity glaze film during the sintering process, which ensures the bonding strength between the glaze layer and the metal blank, while also reducing the erosion of condensates, making the glaze surface resistant to acid and alkali corrosion; When the copper powder is replaced with silver powder, since the thermal expansion coefficient of the silver powder is higher than that of the stainless steel metal body, the fired glaze surface is prone to cracking or falling off, so the present application preferably uses copper powder.
[0058] When calcium carbonate is used to replace sodium carbonate, due to its high melting point, calcium carbonate cannot play a fluxing effect at the firing temperature of this application. The glaze film is difficult to fully penetrate into the surface of the metal body under high temperature environment, so the bonding strength of the formed glaze is poor.
[0059] When bentonite is used to replace hydroxyapatite, the acid resistance of the glaze, the bonding strength with the blank and the condensate adhesion test are not as good as hydroxyapatite. This is because sodium fluoride can react with hydroxyapatite to form fluoroapatite, which enhances the acid resistance of the glaze and reduces the corrosion of the condensate to the metal square tube. Hydroxyapatite is a material that is closer to the thermal expansion coefficient of the metal blank of this application, so that the spraying material can be tightly solidified on the surface of the metal blank after sintering, and the copper powder can form a flexible and low-porosity glaze film during the firing process.
[0060] It can be seen from Application Examples 1.3 and 2.1-2.3 and from Tables 2 and 3 that the glaze surface and the metal body have good bonding strength and acid resistance, indicating that the addition of sodium fluoride to the spraying material in the present application, on the one hand, helps to promote the rapid solidification of silicate cement, forming a stable glaze layer during the drying process of the metal body, and then forming a dense and uniform glaze surface after firing; on the other hand, since the condensate in the coke oven raw gas is acidic, sodium fluoride can react with hydroxyapatite to form fluoroapatite, thereby enhancing the acid resistance of the glaze surface, reducing the corrosion of the condensate to the metal square tube, and extending the service life of the square tube.
[0061] Combining Application Examples 1.3, 3 and 4.1-4.4 and Table 2, it can be seen that the addition of diatomaceous earth-loaded copper powder helps the thermal expansion coefficients of the spraying material and the metal body to be close, which in turn helps to form a dense glaze with good bonding with the metal body after sintering.
[0062] In addition, the particle size of the diatomite-loaded copper powder is within the range of 40-60 μm, the spraying material and the metal body have a better bonding effect after firing, and the formed glaze has better density and strength.
[0063] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high temperature resistant spraying material for metal surface, characterized in that: The powder comprises the following parts by weight: Barium carbonate 10-20 parts; 10-20 parts of sodium carbonate; 15-25 parts of titanium dioxide; 5-10 parts of Portland cement; 30-50 parts of copper powder; Hydroxyapatite 5-15 parts.
2. A high temperature resistant spraying material for metal surface according to claim 1, characterized in that: The powder comprises the following parts by weight: Barium carbonate 12-18 parts; 13-17 parts of sodium carbonate; 18-23 parts of titanium dioxide; 7-9 parts of Portland cement; 35-45 parts of copper powder; Hydroxyapatite 8-13 parts.
3. A high temperature resistant spraying material for metal surface according to claim 1 or 2, characterized in that: It also includes 15-20 parts of sodium fluoride.
4. The high temperature resistant spraying material for metal surface according to claim 1, characterized in that: The copper powder is diatomite-loaded copper powder, and its preparation method comprises the following steps: The diatomaceous earth is placed in a hydrochloric acid solution, shaken in a constant temperature water bath, and then washed with water until neutral to obtain pretreated diatomaceous earth. The pretreated diatomaceous earth is dispersed in an ethanol solution, and copper powder is added. The weight ratio of copper powder to diatomaceous earth is 1: (1.1-1.2). Ultrasonic shaking is performed for 1-2 hours, and then filtration and drying are performed to obtain diatomaceous earth-loaded copper powder.
5. A high temperature resistant spraying material for metal surface according to claim 4, characterized in that: The particle size of the diatomaceous earth-loaded copper powder is 40-60 μm.
6. A method for preparing a high temperature resistant spraying material for metal surface according to any one of claims 1 to 5, characterized in that: The following steps are involved: Barium carbonate, sodium carbonate, titanium dioxide, silicate cement, copper powder, hydroxyapatite and sodium fluoride are weighed in proportion, and then ground and mixed at a grinding speed of 200-220 rpm and a mixing time of 15-20 min. After mixing, the mixture is sieved to obtain a powder with uniform particles.
7. An application of the high temperature resistant spraying material for metal surface according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Mix the powder and water in a certain proportion to obtain a slurry, and adjust the water content of the slurry to 50%-55%; S2, spraying the slurry evenly on the metal body through a spraying device to form a glaze film with a thickness of 0.2-0.4 mm; S3. The sprayed metal body is dried and then sintered at a high temperature. Nitrogen is introduced during the sintering process. The sintering temperature is 1050-1090°C and the temperature is kept for 10-12 hours to form a dense glaze surface on the surface of the metal body.
8. The use of the high temperature resistant spraying material for metal surface according to claim 7, characterized in that: The metal blank in S2 is 310S stainless steel, and the thermal expansion coefficient of the 310S stainless steel is 18.7 μm / m·K.
Citation Information
Patent Citations
Object made of metals that form scale when exposed to heat with protection against scaling and method for its manufacture
CH434924A
Acid-resistant and heat-resistant inorganic anticorrosive coating and preparation method thereof
CN111074276A
Glass lining glaze, anticorrosive coating in oil field pipeline and preparation method of anticorrosive coating
CN112408790A
System and method for increasing the bond strength between a structural material and its reinforcement
US20070264527A1
